Rectal puncture complicating caudal blockade in a child with severe rectal distension. Issue 10 (7th July 2015) - Sathianathan, Vivian; Dobby, Nadine; Polaner, David
Summary We describe a case of unrecognized rectal puncture following unsuccessful caudal blockade in a patient later found to have marked rectal distension on MRI. This may have contributed to the rectal injury.